NATURAL FRUITS BEVERAGES: MARKET OUTLOOK, FUNCTIONAL AND NUTRITIONAL COMPONENTS - CAMARGO, GISELE ANNE; CONSOLI, LARISSA; LELLIS, IVY CRISTINI SOUSA; MIELI, JULIANA; SASSAKI, ÉRICK KINOSHITA (Revista Brasileira de Engenharia de Biossistemas, 2007)
This review involves the market outlook and main functional and nutritional componentsof the juices and fruits beverages. In spite of the fact that high prices are still a majorobstacle for the low social classes; due to the growing demand for healthier foods, thefunctional drinks market has been increasing significantly among consumers. Theprocessing of these drinks must be adequate to the functional label of the product, warrantedby the preservation of natural components in raw material during the processing stages(constantly improved for fulfilling this objective) and by the use of naturally healthy additives.The knowledge of the market’s trends and new opportunity is important for the researchdirection the development and innovation in the sector of drinks, fruit juices and pulps.